TEACHERS’ PERCEPTION REGARDING CLASSROOM ASSESSMENT IN SCHOOL-BASED CURRICULUM - Felicia Miranda Lekatompessy (JURNAL TAHURI, 2017)
Classroom Assessment (CA) involves students and teachers in the continuous monitoring of students' learning (Angelo and Cross, 1993) as it provides teacher with feedback about their effectiveness as teachers, and it gives students a measure of their progress as learners. For many instructors, assessment just means grading, but it actually entails much more than this. When designed thoughtfully and implemented carefully, assessments can provide important evidence about what and how students are learning and whether course goals have been met. This study was intended to explore teachers’ perception regarding classroom assessment that implemented in school-based curriculum, and also to identify the teachers’ experience in conducting classroom assessment. The data were collected from questionnaire of two sections. The first section consists of twenty five items exploring teachers’ perception on classroom assessment in school-based curriculum. While the second section consists of 15 items that deal with the way teachers conduct CA based on their experience. Therefore, three English teachers who implemented school-based curriculum were chosen as the subject of the study. The result indicated that teachers have a comprehensive understanding toward classroom assessment regarding its principles and teachers role in classroom assessment. Further, in implementing the CA, the teachers also used various techniques and methods such as portfolio and performance assessment instead of relied on pen and paper test only.